Evaluation of urinary 1-hydroxypyrene, S-phenylmercapturic acid, trans,trans-muconic acid, 3-methyladenine, 3-ethyladenine, 8-hydroxy-2′-deoxyguanosine and thioethers as biomarkers of exposure to cigarette smoke - Feng, S.; Roethig, H. J.; Liang, Q.; Kinser, R.; Jin, Y.; Scherer, G.; Urban, M.; Engl, J.; Riedel, K. (Biomarkers, 2006)
Abstract The objective was to evaluate the utility of urinary 1-hydroxypyrene (1-OHP), S-phenylmercapturic acid (S-PMA), trans,trans-muconic acid (t,t-MA), 3-methyladenine (3-MeAd), 3-ethyladenine (3-EtAd), 8-hydroxy-2′-deoxyguanosine (8-OHdG) and thioethers as biomarkers for assessing the exposure in adult smokers who switched from smoking conventional cigarettes to candidate potential reduced exposure products (PREP) or who stopped smoking. Two electrically heated smoking systems (EHCSS) were used as prototype cigarettes that have significant reductions in a number of mainstream smoke constituents as measured by smoking machines relative to those from conventional cigarettes. Urine samples were collected from a randomized, controlled, forced-switching study in which 110 adult smokers of a conventional cigarette brand (CC1) were randomly assigned to five study groups. The groups included the CC1 smoking group, a lower-tar conventional cigarette (CC2) smoking group, EHCSS1 group, EHCSS2 group and a no smoking group that were monitored for 8 days. Biomarkers were measured at baseline and day 8. The daily excretion levels of these biomarkers were compared among the groups before and after switching, and the relationships between the daily excretion levels of these biomarkers and cigarette smoking-related exposure were investigated using Pearson product-moment correlation and multiple regression analyses. It was concluded that under controlled study conditions: (1) 1-OHP, S-PMA and t,t-MA are useful biomarkers that could differentiate exposure between smoking conventional and EHCSS cigarettes or between smoking conventional cigarettes and no smoking; between S-PMA and t,t-MA, the former appeared to be more sensitive; (2) 3-MeAd could only differentiate between smoking conventional cigarettes and no smoking; the results for 3-EtAd were not conclusive because contradictory results were observed; (3) 8-OHdG had a questionable association with smoking and therefore the utility of this biomarker for smoking-related exposure could not be established; and (4) urinary excretion of thioethers as a biomarker lacked sensitivity to demonstrate a clear dose-response relationship in conventional cigarette smokers, although it could differentiate the excretion levels between those subjects who smoked a conventional cigarette and those who stopped smoking.